Endovascular embolization of arterial bleeding in patients with severe acute pancreatitis - Ai, Min (Wideochir Inne Tech Maloinwazyjne, 2019)
INTRODUCTION: Severe acute pancreatitis (SAP) has a high mortality rate of 20% to 30%, with death often resulting from hemorrhage. AIM: To investigate the role of digital subtraction angiography (DSA) and endovascular embolization in the management of arterial bleeding in SAP patients. MATERIAL AND METHODS: Seventy-six patients with SAP admitted to our hospital between January 2010 and May 2016 underwent DSA. DSA revealed arterial bleeding in 22 of these patients, who were treated with transcatheter endovascular embolization with coils and/or gelfoam particles. Patient demographics, angiographic features of vascular abnormalities, and outcomes of embolization were assessed. RESULTS: Arterial bleeding was the most common vascular abnormality (22/76 patients; 28.9%). DSA enabled the identification of 27 bleeding arteries in 22 patients. The splenic artery was the most commonly affected vessel (11/27; 40.7%). Among the 27 arteries treated with endovascular embolization, successful hemostasis was achieved in 96.3% (26/27). Two patients developed major complications (hepatic and splenic abscess). These patients were treated with abdominal catheter drainage and anti-infection measures and ultimately recovered. The mean interval between initial onset of SAP and angiographic diagnosis of arterial bleeding was 56 days. Rebleeding was diagnosed in 5 patients (5/22; 22.7%) during repeat angiography, with bleeding from new sites in four of these patients. The mean interval between successive angiography treatments was 38 days. CONCLUSIONS: Endovascular embolization is a safe and effective method to localize bleeding arteries and achieve complete hemostasis in patients with SAP-related arterial bleeding.